Clinical aspects of people with chronic renal failure in conservative treatment - Camila Castro Roso; Margrid Beuter; Jamile Lais Bruinsma; Júlia Heinz da Silva; Arlete Maria Brentano Timm; Macilene Regina Pauletto (Rev Rene)
This study aimed to describe the social and clinical needs of people with chronic renal failure on conservative treatment in an outpatient uremia in southern Brazil. It is a research descriptive, developed with 15 people. Data were collected from march to may 2011, through the documentary analysis and experiences of narrative interview. The age ranged from 19 to 85 years and it was evident that most participants have underlying disease as hypertension and diabetes mellitus. In conclusion that laboratory abnormalities are related to worsening of renal function, worsening of cardiovascular disease and increased morbidity and mortality. The conservative treatment reduction in the rate of disease progression, maintaining renal function and improving the clinical, psychological and social people. The nurse can develop health education activities effective in promoting the health of these people.